CCR4 is critically involved in effective antitumor immunity in mice bearing intradermal B16 melanoma. Issue 1 (1st August 2016) - Matsuo, Kazuhiko; Itoh, Tatsuki; Koyama, Atsushi; Imamura, Reira; Kawai, Shiori; Nishiwaki, Keiji; Oiso, Naoki; Kawada, Akira; Yoshie, Osamu; Nakayama, Takashi
Highlights: CCR4-deficient mice displayed enhanced tumor growth upon the inoculation of B16-F10. CCR4-deficient mice have reduced tumor-infiltrating CD8+ effector T cells. CCR4-deficient mice have reduced DC-Th17 cell clusters and Th17 cell expansion. Administration of a CCR4 antagonist enhanced tumor growth and decreased Th17 cells. The deficiency of CCR6 did not affect tumor growth and the number of Th17 cells. Abstract: CCR4 is a major chemokine receptor expressed by Treg cells and Th17 cells. While Treg cells are known to suppress antitumor immunity, Th17 cells have recently been shown to enhance the induction of antitumor cytotoxic T lymphocytes. Here, CCR4-deficient mice displayed enhanced tumor growth upon intradermal inoculation of B16-F10 melanoma cells. In CCR4-deficient mice, while IFN-γ+CD8+ effector T cells were decreased in tumor sites, IFN-γ+CD8+ T cells and Th17 cells were decreased in regional lymph nodes. In wild-type mice, CD4+IL-17A+ cells, which were identified as CCR4+CD44+ memory Th17, were found to be clustered around dendritic cells expressing MDC/CCL22, a ligand for CCR4, in regional lymph nodes. Compound 22, a CCR4 antagonist, also enhanced tumor growth and decreased Th17 cells in regional lymph nodes in tumor-bearing mice treated with Dacarbazine. In contrast, CCR6 deficiency did not affect the tumor growth and the numbers of Th17 cells in regional lymph nodes. These findings indicate that CCR4 is critically involved in regional lymph node DC-Th17 cell interactions that are necessary for Th17 cell-mediated induction of antitumor CD8+ effector T cells in mice bearing B16 melanoma.